PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT TERINTEGRASI CULTURALLY RESPONSIVE TEACHING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA PADA MATERI SIKLUS AIR - Nurlaina; Rezeki Muammar, M.; Fatimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the creative thinking of fifth grade students of UPTD SD Negeri 13 Jangka through the application of the Teams Games Tournament learning model. The background of the study shows that students' creative thinking abilities are still relatively low, especially in understanding the water cycle material. The low ability of students' creative thinking on the material is seen from the learning process which is still one-way, where the teacher is more dominant in explaining the material while students tend to be passive in listening without much participation. This Classroom Action Research (CAR) was carried out in two cycles. The results of the study showed a significant increase in creative thinking abilities with classical completeness increasing from 34.61% in cycle I to 88.46% in cycle II. In addition, teacher activity increased from 77.7% to 95.25% and student activity increased from 75.3% to 91.45%. Student responses to the Teams Games Tournament (TGT) learning model were also very positive, with 78.46% responding strongly agree (SS), 13.84% agreeing (S), 6.92% disagreeing (TS), and 0.76% strongly disagreeing (STS). Thus, the Teams Games Tournament (TGT) learning model has proven effective in enhancing students' creative thinking skills, particularly in understanding the water cycle, as well as creating a more active and positive learning environment.